THE EFFECT OF SERVICE PRICE AND QUALITY ON CUSTOMER SATISFACTION ONLINE TRANSPORTATION SERVICES - Aeny, Nur; Ekhsan, Muhamad; Tanjung, Agustini (Journal of Research in Business, Economics, and Education, 2019)
One of the service businesses that are currently developing is the two-wheeled transportation service business or often referred to as a motorcycle taxi. One of these motorcycle taxi companies is Grab Bike; Grab Bike is a provider of online motorcycle taxi service that always provides what we need, especially people who are tired of traffic jams. Does the price partially affect customer satisfaction online motorcycle taxi services (study of Grab Bike consumers in South Cikarang region)? Does service quality partially affect customer satisfaction with online motorcycle taxi services (a study of Grab Bike consumers in South Cikarang region)? Does service quality and price simultaneously influence customer satisfaction with online motorcycle taxi services (a study of Grab Bike consumers in South Cikarang region)? This type of research is quantitative research. The sample collection technique uses nonprobability sampling technique with accidental sampling approach. Data was collected using a survey method through a questionnaire filled out by respondents and interviews in person. The research sample used was 50 respondents. This study uses multiple linear regression analysis methods. Hypothesis testing using the F test and T-test. The results of research using the T-test note that price significantly influences customer satisfaction, while service quality significantly influences customer satisfaction; this shows the most dominant variable in influencing customer satisfaction is the price variable. While the results of the study using the F test the price and service quality variables have a simultaneous influence on customer satisfaction.